Unmet healthcare needs and related factors according to gender differences in single-person households - Hyun Ju Chae; Mijong Kim (Korean Society of Women Health Nursing, 2020)
Purpose This study was conducted to identify unmet healthcare needs among man and woman one-person households and to explore related factors by gender. Methods Data were drawn from the 2017 Korea National Health and Nutrition Examination Survey. The final sample consisted of 820 one-person households. The statistical analysis, conducted in SPSS version 20.1, included complex sampling analysis; descriptive statistics, the chi-square test, and logistic regression. Results The demographic and socioeconomic characteristics of women in one-person households were significantly different from those of men in one-person households. Women in single-person households were mainly in their 70s or older and married, and they tended to have a low education level, low income, and no formal occupation. Unmet healthcare needs were experienced by 17.3% of women in one-person households and 13.5% of men in one-person households, which was not a statistically significant difference (χ2=2.17, p=.139). Factors related to unmet healthcare needs were subjective health status and unmet dental care needs in single-person-household men. By contrast, having experienced impairment within the past year, stress, and unmet dental care needs were factors related to unmet healthcare needs in single-person-household women. Conclusion As one-person households become increasingly common, more attention needs to be paid to them and our understanding of them needs to be improved. Women in one-person households, in particular, are especially vulnerable, as they experience more unmet healthcare needs.